2013
DOI: 10.1371/journal.pone.0056190
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotial Formation of Polyporus umbellatus by Low Temperature Treatment under Artificial Conditions

Abstract: Background Polyporus umbellatus sclerotia have been used as a diuretic agent in China for over two thousand years. A shortage of the natural P. umbellatus has prompted researchers to induce sclerotial formation in the laboratory.Methodology/Principal Finding P. umbellatus cultivation in a sawdust-based substrate was investigated to evaluate the effect of low temperature conditions on sclerotial formation. A phenol-sulfuric acid method was employed to determine the polysaccharide content of wild P. umbellatus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…During P. umbellatus sclerotial formation, the fungus relies on antioxidant mechanisms to neutralize the excessive reactive oxygen species26. On one hand, the sclerotial exudate consists of fatty acids, ammonia, proteins and various enzymes, including the antioxidant enzymes peroxidase and catalase31.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During P. umbellatus sclerotial formation, the fungus relies on antioxidant mechanisms to neutralize the excessive reactive oxygen species26. On one hand, the sclerotial exudate consists of fatty acids, ammonia, proteins and various enzymes, including the antioxidant enzymes peroxidase and catalase31.…”
Section: Discussionmentioning
confidence: 99%
“…4, panel A) under the same cultivation conditions. This is probably because the P. umbellatus mycelia formed sclerotia to adapt to the hyperoxidant conditions by increasing the oxalic acid concentration and avoiding the oxidative stress state2638. It is generally reasonable to assume that oxalic acid serves as an antioxidant during sclerotial differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and development of sclerotia are associated with a series of signaling genes, such as reports in S. sclerotiorum that the microbial opsin homolog gene sop1 was involved in sclerotial development and virulence of this fungus (Lyu et al, 2015). Previous studies have shown that sclerotial development in some fungi was associated with and affected by a series of physical, chemical or nutritional factors, such as low temperatures, oxidative stress and low PH (Chet and Henis, 1975; Choi et al, 2002; Xing et al, 2013). In addition, the cAMP and the mitogen-activated protein kinase (MAPK) signal pathways are involved in sclerotial development of S. sclerotiorum (Rollins and Dickman, 1998; Chen et al, 2004), and this process also requires calcineurin in an oxalic-acid-independent manner (Harel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The triterpenoid concentration was detected with ursolic acid as the standard product by vanillin colorimetry at 546nm [37]. The polysaccharide content was measured using the phenol-sulfuric acid method at 490nm based on a standard curve for glucose [38].…”
Section: Determination Of Active Compoundsmentioning
confidence: 99%